A core curriculum of point-of-care ultrasound examinations for frontline physicians in primary care: results from a European Delphi study - Andersen, Camilla Aakjær; Løkkegaard, Thomas; Nayahangan, Leizl Joy; Edwards, Hazel; Iacob, Mihai Sorin; Lebedevaite, Kristina; Kosiak, Mateusz; Gheorghe, Elena Codruta; Salim, Adib; Rüttermann, Viktor; Ewertsen, Caroline; Jenssen, Christian (Ultraschall in der Medizin - European Journal of Ultrasound, 2025)
Point-of-care ultrasound (PoCUS) has found its way into primary care in some, but not all, European countries. A prerequisite for achieving Europe-wide comparable diagnostic reliability of PoCUS performed by primary care physicians is high-quality training that is limited to relevant, frequently encountered PoCUS applications that are easy to learn and master. A European Federation of Societies for Ultrasound in Medicine (EFSUMB) task force performed a brainstorming exercise to identify all possible ultrasound examinations that could be performed in primary care. A 3-stage Delphi process was launched. The Delphi panelists were 95 primary care physicians from 28 European countries with more than 2 years of experience using and teaching ultrasound. Solely focusing on the complexity of performing PoCUS, the panelists reduced the brainstorming list in a stepwise manner to a basic core curriculum intended for primary care frontline physicians including 40 diagnostic PoCUS examinations within 13 different anatomical areas and no ultrasound-guided procedures. A 75% cut-off was used for agreement. Despite the great heterogeneity of the Delphi panel representing different views and contexts from across Europe, kappa statistics showed substantial or moderate agreement across Delphi rounds 2 and 3 for 85% of the 40 diagnostic PoCUS applications. The results of this study offer guidance for EFSUMB to establish training recommendations for a basic core curriculum that can be adapted to the needs of different regions of Europe and thus create a basis for PoCUS to become a reliable diagnostic tool in primary care across Europe, based on common quality standards.
Keywords: Point-of-care Ultrasound; General Practice; Family Medicine; Primary Healthcare; Curriculum